Juror - Mouzouropoulos, Theseas (My University, 2026)
Juror at the International Motion Festival judging motions graphics, kinetic typography, broadcast commercials and animations. The IMF aims to open a forum for the presentation of the most contemporary and most creative work in the world of motion and thus to be established as the Pioneering Festival that promotes innovative and cutting-edge work.